Investigation of the effects of Huyet Rong germinated red rice on gene expression in diabetic mouse - Nguyen, Duc Quan; Nguyen, Dieu Linh; Tran, Thi Huong Giang; Nguyen, Kim Thoa; Le, Tien Nga; Do, Thi Thanh Trung; Nguyen, Quang Huy; Le, Tat Thanh; Nguyen, Huy Hoang (Vietnam Journal of Biotechnology, 2024)
Diabetes mellitus is an autoimmune disease that causes hyperglycemia due to the destruction of pancreatic beta cells and deficiency in insulin synthesis. Rates of diabetes increased from 2.7% in 2002 to 5.4% in 2012 and 7.3% in 2020, making it the 7th most leading cause of death in Vietnam. Many studies have shown that dietary change can help alleviate the disease symptoms via improving metabolic control, dyslipidemia, and oxidative stress levels. Huyet Rong red rice, a domesticated rice cultivar rich in vitamins, essential trace elements, antioxidant polyphenols, fiber and a low glycemic index in nature, has become an attractive diet for patients with diabetes. For these reasons, this study aims to investigate the effects of Huyet Rong germinated red rice on the expression of diabetic associated genes, GLUT-2, GLUT-4, IR, IRS1, NFKB1, and GSK-3, in diabetic mouse models using the RT-qPCR method. Our findings reveal that the germination process has significantly increased the level of antioxidant agents, g-oryzanol and g-aminobutyric acid, in Huyet Rong red rice grains, rising by 1.2 and 15.1 folds, respectively. RT-qPCR analysis also reveals that the diet supplemented with germinated Huyet Rong red rice flour possesses some positive effects on the STZ-induced mice via increasing the expression of GLUT2, NFKB1, IRS1, and GSK-3 that are involved in glucose transportation, insulin signaling, and inflammatory and oxidative responses.